Design and Development of Mathematics and Basic Indonesian Learning Tools for Early Children Based on Android - Masrizal; Syaiful Zuhri Harahap; Musthafa Haris Munandar; Irmayanti; Aisyah Hayati (Jurnal Mantik, 2020)
It is media learning. Using advanced Android smartphones also evolved from manual to digital learning media. However, the rapid development of the era does not shed light on advancing learning methods in the educational institution, as PAUD Kamboja, Tanjung Gadang Sub- District, which still uses manual learning methods today. PAUD Kamboja needs different media to help the learning process, such as using digital media as android applications. Actionscript 3.0 is designed and built using Adobe Flash Professional CS6 software and language. Support is also an android-based AdobeAIR application, used as a drive or runtime.